Statistical Analysis for Packed Milk Buying Behaviour - Sharma, Yogesh Kumar; Patil, Pravin P.; Mangla, Sachin Kumar (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920529);" role="presentation">Packed milk of different brands and configuration are available in the market. Normally buyer faces the problem <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916772);" role="presentation">during the selection of suitable brand according to his/her requirement. In the present study, <span dir="ltr" style="left: calc(var(–scale-factor)*445.30px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984259);" role="presentation">IBM 14.5 <span dir="ltr" style="left: calc(var(–scale-factor)*487.42px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901274);" role="presentation">Statistics <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905981);" role="presentation">Package for the Social Scienc<span dir="ltr" style="left: calc(var(–scale-factor)*192.17px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903053);" role="presentation">es (SPSS) software is used to analyse the buyer behaviour towards <span dir="ltr" style="left: calc(var(–scale-factor)*464.38px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901658);" role="presentation">the purchasing <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947327);" role="presentation">packed milk <span dir="ltr" style="left: calc(var(–scale-factor)*125.18px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881554);" role="presentation">based on <span dir="ltr" style="left: calc(var(–scale-factor)*164.66px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938138);" role="presentation">twelve <span dir="ltr" style="left: calc(var(–scale-factor)*194.57px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900377);" role="presentation">parameters. Dataset is created using <span dir="ltr" style="left: calc(var(–scale-factor)*344.59px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9965);" role="presentation">IBM 14.5 <span dir="ltr" style="left: calc(var(–scale-factor)*387.67px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905933);" role="presentation">SPSS software and the data were <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915522);" role="presentation">collected through questionnaire from employees around Uttarakhand. <span dir="ltr" style="left: calc(var(–scale-factor)*355.15px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899241);" role="presentation">Pr<span dir="ltr" style="left: calc(var(–scale-factor)*364.15px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900211);" role="presentation">esent study uses the correlation method <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906098);" role="presentation">to ascertain the influence of parameters on buyers packed milk purchasing behaviour.